Insecticidal and Acetylcholinesterase Inhibition Activity of Veratrum nigrum Alkaloidal Extract against the German Cockroach (Blattella germanica) - Xianghai Cai; Qingfeng Li; Lei Xiao; Hailiang Lu; Jian Tang; Jianbo Huang; Jianzhong Yuan (Journal of Arthropod-Borne Diseases, 2018)
Background: Veratrum nigrum (Liliaceae) is perennial medicinal plant widely used to treat various conditions. To determine its insecticidal properties against the German cockroach (Blattella germanica), several laboratory tests were carried out.